2015
DOI: 10.1016/j.compfluid.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of surface acoustic wave actuated enantiomer separation by the finite element immersed boundary method

Abstract: Abstract. Enantiomers are chiral objects such as chemical molecules that can be distinguished by their handedness. They typically occur as racemic compounds of left-and right-handed species which may have completely different properties. Therefore, in applications such as drug design in pharmacology, enantiomer separation is an important issue. Here, we present a new technology for enantiomer separation by surface acoustic wave generated vorticity patterns consisting of pairwise counter-rotating vortices in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…On the other hand, as shown in Figure 29 shows that a right-handed (left-handed) enantiomer initially placed a little bit to the right of the middle between the two counter-rotating vortices gets attracted by the counter-clockwise (clockwise) rotating vortex in the upper-right (lower-right) quadrant. This behavior is in accordance with experimental measurements and similar to numerical simulation results that have been obtained for deformable L-shaped enantiomers by an application of the FEIBM [5]. We note that [5] also contains numerical results for multiple enantiomers of different handedness which confirm the separation mechanism described above.…”
Section: Numerical Simulation Of Enantiomer Separationsupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, as shown in Figure 29 shows that a right-handed (left-handed) enantiomer initially placed a little bit to the right of the middle between the two counter-rotating vortices gets attracted by the counter-clockwise (clockwise) rotating vortex in the upper-right (lower-right) quadrant. This behavior is in accordance with experimental measurements and similar to numerical simulation results that have been obtained for deformable L-shaped enantiomers by an application of the FEIBM [5]. We note that [5] also contains numerical results for multiple enantiomers of different handedness which confirm the separation mechanism described above.…”
Section: Numerical Simulation Of Enantiomer Separationsupporting
confidence: 89%
“…After soft baking, the photoresist is exposed using a mask aligner and then baked a second time (4). After the substrate has cooled to room temperature, the unexposed photoresist is developed using MR-DEV300 leaving the desired particles attached to the sacrificial layer of omnicoat (5). In order to render the particles hydrophobic on one side, a layer of Trichloro(octadecyl)silane (OTS) is applied by spin coating (6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For such relatively large particles, the effects of thermal fluctuations are negligibly small. Both studies 32,33 consistently predicted that these enantiomers are separated in the 4-vortex flow according to their handedness when injected into the flow approximately in the middle between two counter-rotating vortices, because Two earlier studies 35,36 had investigated flexible chiral particles, which are built of "atoms" connected by elastic springs, when moving in three-dimensional uniform shear flows. For helical particles, Talkner et al 36 showed from numerical simulations that hydrodynamic interactions between the component "atoms" (via the Rotne-Prager mobility tensors) lead to mechanically induced drift in a direction lateral to the shear plane, which depends on the chirality of the object and the sign of the shear rate.…”
Section: Above)mentioning
confidence: 91%
“…Concerning hydrodynamic interactions, two follow-up studies 32,33 analysed the same 4-vortex flow pattern and its potential for chiral separation employing two different computational methods, which both allow for a full hydrodynamic treatment of the problem. The first study 32 uses a so-called fictitious domain Lagrange multiplier method, which has been developed specifically to capture the deterministic motion of rigid particles in carrier fluids.…”
Section: Above)mentioning
confidence: 99%